CONSTRUCTING A CRYPTO ASSET REGULATORY FRAMEWORK: BRIDGING SHARIAH FATWAS AND INDONESIAN POSITIVE LAW - Hardyansah, Rommy; Darmawan, Didit; Putra, Arif Rachman; Vitrianingsih, Yeni (Gapenas Publisher, 2025)
This literature study critically examines the intersection between Shariah rulings (fatwas) and positive law regulations concerning crypto assets in Indonesia. The research aims to analyze the methodology of legal derivation (istinbath) used in major fatwas, identify points of convergence and divergence with national regulations, and formulate an integrative regulatory model. Through a qualitative normative analysis of fatwa documents, regulations from the Commodity Futures Trading Regulatory Agency (Bappebti), and related legal frameworks, the study reveals that Shariah rulings predominantly prohibit crypto investment due to dominant elements of gharar (excessive uncertainty), maysir (gambling/speculation), and weak maliyyah (asset legitimacy). In contrast, positive law treats crypto as a tradable commodity under a risk-management framework. The significant divergence lies in the classification of objects and levels of precaution, while convergence exists in the shared goals of consumer protection and market integrity. To bridge this gap, the study proposes a layered model of substantive harmonization. This model involves refining legal classifications to accommodate Shariah utility criteria, establishing an explicit Shariah compliance pathway with certification mechanisms, strengthening risk disclosure standards aligned with Shariah transparency principles, and fostering institutional synergy between financial regulators and Shariah authorities. This approach seeks to align regulatory objectives with core Islamic principles without negating secular governance goals, offering a blueprint for a more ethical and stable crypto asset ecosystem in Muslim-majority jurisdictions.